2014
DOI: 10.4103/0019-509x.175367
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of systemic bacterial infections during febrile neutropenia in pediatric oncology patients in tertiary care pediatric center

Abstract: Gram-negative organism is a common isolate in cancer children with febrile neutropenia, which is resistant to first-line antibiotic cefepime. Meropenem is most sensitive antibiotic and ESBL's are sensitive to piperacillin-tazobactam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 0 publications
3
25
0
1
Order By: Relevance
“…CONS comprised 85.7% of the Gram-positive isolates. Siddaiahgari et al (26) reported Gram-negative isolates in 85.3% of positive blood or urine cultures, with E. coli and Pseudomonas aeruginosa being the most common pathogens. Karanwal et al Half of the CONS were methicillin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…CONS comprised 85.7% of the Gram-positive isolates. Siddaiahgari et al (26) reported Gram-negative isolates in 85.3% of positive blood or urine cultures, with E. coli and Pseudomonas aeruginosa being the most common pathogens. Karanwal et al Half of the CONS were methicillin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…The changing microbiological spectrum, in febrile neutropenia and the resistance patterns, help guide antibiotic treatment. [7] Audit of febrile neutropenic episodes, would help guide treatment protocols to reduce the mortality and improve outcomes. We conducted a single centre prospective study aimed at identifying the trends in the pattern of microbiological isolates and sensitivity patterns for episodes of febrile neutropenia in the paediatric oncology unit of a tertiary care teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The same has been echoed in the study by Mikulska et al [30], who found that a questionnaire based data obtained in 2011 reported predominance of Gram negative organisms compared to the published data between 2005-2011. It is also worth mentioning that the studies from developing countries such as India [12][13][14][21][22][23][24][25][26] have consistently demonstrated a predominance of Gram negative organisms, probably because of less use of central venous catheters. It is not only the predominant organism but their antibiotic sensitivity pattern that decide the choice of empirical antimicrobial therapy in children with FN.…”
Section: Introductionmentioning
confidence: 99%
“…Trimethoprim/sulfamethoxazole, amoxicillin/clavulanate and fluoroquinolones have been used as antibacterial prophylaxis in these children with success, but has been linked with the risk of emergence of antibiotic resistance [1]. Past several decades have witnessed substantial change in the bacterial etiology of pediatric febrile neutropenia ( Apart from the time period of study, the microbiology of febrile neutropenia is largely dependent on the regional differences based on socio-economic and healthcare developments [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Data from European Organization for Research and Treatment of Cancer (EORTC) during 1973-1994, reveals a decreasing incidence of Gram negative agents from 71% to 31% while Gram positive infection rose from 29% to 69% [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation